Mortality profile of confirmed cases of swine flu attending a tertiary care center of Udaipur region of Rajasthan, India - Singhal, Yogesh Kumar; Kothari, Nitin (International Journal of Advances in Medicine, 2019)
Background: Mortality profile is an analytical tool used to identify the various factors responsible for poor outcome of disease and it can also use to evaluate quality and efficiency of healthcare providers. The aim of this study is to summarise the clinical and epidemiological factors as well as to identify the risk factors associated with mortality among swine flu cases. Methods: It is a cross-sectional, descriptive, hospital-based study conducted on 62 deceased patients due to swine flu reported at Maharana Bhupal Government Hospital, Udaipur, Rajasthan during the outbreak of influenza A H1N1 in the year 2015. A standardized pre-structured questionnaire with consent was filled by help of bed head tickets and by interview of attendants of deceased patients. Results: Deaths were higher among age group of 31-45 years (35.48%). Case fatality rate for male patients (13.88%) was higher. Mortality was highest in females of rural background 27(43.55%). Majority of deceased patients (70.97%) had delay of 4-7 days in admission after onset of symptoms. Diabetes, cardiovascular diseases and pregnancy was the major risk factors for poor outcome. Conclusions: Delay in diagnosis and admission may be the reason for higher mortality rate. The most common co morbid illness was Diabetes mellitus, cardiovascular diseases (Ischemic heart disease, Rheumatic heart disease, Hypertension) and pregnancy.